Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/biomedicines10092236
|View full text |Cite|
|
Sign up to set email alerts
|

Probiotic-Based Intervention in the Treatment of Ulcerative Colitis: Conventional and New Approaches

Abstract: Although there are number of available therapies for ulcerative colitis (UC), many patients are unresponsive to these treatments or experience secondary failure during treatment. Thus, the development of new therapies or alternative strategies with minimal side effects is inevitable. Strategies targeting dysbiosis of gut microbiota have been tested in the management of UC due to the unquestionable role of gut microbiota in the etiology of UC. Advanced molecular analyses of gut microbiomes revealed evident dysb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 198 publications
0
15
0
Order By: Relevance
“…Levels of inflammatory cytokines and recurrence rates leading to repeat surgery were lower among patients who received early VSL#3 (for the entire 365 days). This indicated that this probiotic should be further investigated for prevention of Crohn's disease recurrence [94,95].…”
Section: Inflammatory Bowel Disease and Probioticsmentioning
confidence: 99%
“…Levels of inflammatory cytokines and recurrence rates leading to repeat surgery were lower among patients who received early VSL#3 (for the entire 365 days). This indicated that this probiotic should be further investigated for prevention of Crohn's disease recurrence [94,95].…”
Section: Inflammatory Bowel Disease and Probioticsmentioning
confidence: 99%
“…Probiotics help maintain remission for a longer time and improve the quality of life for ulcerative colitis patient. 4 …”
Section: Dear Editormentioning
confidence: 99%
“… 1 The method used has been able to assess the effectiveness of intestinal microbiota transplantation, however I recommend adjunctive therapy such as administration of conventional probiotic strains with common approaches applied in disease management to modify gut microbiota, improve gut barrier integrity and function, and maintain a balanced immune response. 4 In addition, intestinal microbiota transplantation can also help doctors predict the success of ulcerative colitis treatment. 5 …”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…According to the de nition of the World Health Organization (WHO), probiotics are living micro-organisms which, when administered in adequate amounts, confer a health bene t on the host. Regarding their proven health bene ts they have been applied in the management of several disease including gastrointestinal disorders like UC (9)(10)(11)(12)(13). Several protective mechanisms have been de ned for probiotics including improvement of intestinal barrier function, secretion of anti-in ammatory and anti-oxidant metabolites, regulation of tissue brosis, alteration of gut microbial composition, and modulation of immune responses (14,15).…”
Section: Introductionmentioning
confidence: 99%